Evaluasi kesesuaian elemen lanskap Taman Balekambang sebagai ruang publik di Kota Surakarta, Jawa Tengah - Tarigan, Doksa Safira; Semarajaya, Cokorda Gede Alit; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap, 2022)
Balekambang Park is one of the most popular public spaces in Surakarta. However, the condition of some of the facilities and plants in Balekambang Park looks poorly maintained. Most of the facilities such as toilets, park benches and trash cans were seen to have been damaged. Apart from that, some of the tree crowns were too shady. This phenomenon has an impact on four aspects of forming public space, which consist of access & linkages, uses & activites, comfort & image and sociability. The deficiencies in the landscape elements of Balekambang Park occur because they are not yet in accordance with these four aspects. Therefore, the evaluation process needs to be carried out to find out which aspects have not been fulfilled. This study aims to evaluate the conditions of hardscape and softscape in Balekambang Park based on four main aspects of forming public spaces and to describe people's perceptions of Balekambang Park as a public space. The method used is a survey method with qualitative descriptive analysis. The data inventory was carried out by observation, interviews and distributing questionnaires. The results showed that the hardscape and softscape elements in Balekambang Park have fulfilled the four main aspects of forming public spaces. The access and linkages aspect is very good, but three other aspects still need to be improved. This is also relevant to the visitor perception questionnaire analysis which explains that the access and linkages aspects are in the high category, while the other three aspects are in the medium category.